Is there an observational effect? An exploratory study into speed cameras and self-reported offending behaviour. (November 2017) - Freeman, J.; Kaye, S-A.; Truelove, V.; Davey, J.
Highlights: The sample reported a high level of exposure to speed cameras. Younger males were most likely to report speeding and be more aware of the presence of speed cameras. Perceived certainty of apprehension was the strongest reported deterrent force. A counterintuitive positive effect was found between camera exposure levels and speeding behaviours. Higher levels of perceptual certainty were linked to general speed compliance. Abstract: Fixed and mobile speed cameras are an important element of enforcement initiatives designed to create a strong deterrent effect and improve road safety. Despite the widespread use of the technology and the need to create a strong deterrent effect, research has yet to determine if there is a relationship between levels of exposure to the devices and subsequent self-reported deterrent effects. As a result, licensed motorists ( N  = 536; 51% female) in Queensland (Australia) were recruited to complete a questionnaire that measured exposure to speed cameras and associated offending behaviours. Data were analyzed utilising descriptive, bivariate and multivariate statistics. The key findings that emerged were: the sample reported a higher level of exposure to fixed cameras (even though there are more operational mobile cameras), younger males were most likely to speed and be observant of speed cameras and that perceived certainty of apprehension was the largest reported deterrent force. However, a positive (rather than negative) relationship was found between perceived camera exposure levels and speeding behaviours, which indicates a range of additional factors (both legal and non-legal factors as well as driving exposure levels) influence speed limit non-compliance. Furthermore, multivariate analysis revealed that higher levels of perceptual certainty were associated with general speed compliance and perceptions of the severity and swiftness of sanctions, rather than levels of self-reported camera exposure. This paper is the first to reveal that while motorists prone to speed may be more cognisant of speed camera operations, this in itself does not ensure appropriate behaviour modification.